Effects of ozone on growth, net photosynthesis and yield of two African varieties of Vigna unguiculata. (January 2015) - Tetteh, Rashied; Yamaguchi, Masahiro; Wada, Yoshiharu; Funada, Ryo; Izuta, Takeshi
Abstract: To assess the effects of O3 on growth, net photosynthesis and yield of two African varieties of cowpea ( Vigna unguiculata L.), Blackeye and Asontem were exposed as potted plants to air that was either filtered to remove O3 (FA), non-filtered air (NF), non-filtered with added O3 of approximately 50 nL L −1 (ppb) from 11:00 to 16:00 (NF + O3 ) for 88 days in open-top chambers. The mean O3 concentration (11:00–16:00) during the exposure period had a range from 16 ppb in the FA treatment to 118 ppb in the NF + O3 treatment. Net photosynthetic rate and leaf area per plant were significantly reduced by exposure to O3, reducing the growth of both varieties. Exposure to O3 significantly reduced the 100-seed weight and number of seeds per pod. As a result, cowpea yield was significantly reduced by long-term exposure to O3, with no difference in sensitivity between the varieties. Highlights: Blackeye responded to O3 at low concentration that was present in NF treatment. In Blackeye, net photosynthesis and leaf area were lower in NF compared to FA. Asontem responded to O3 only in NF + O3 . Abstract : Long-term exposure to O3 reduces growth, net photosynthetic rate and yield of two cowpea varieties.